Effect of acid or laser treatment on degradation of dentin matrix - Üşümez, Aslıhan; Sarı, Tuğrul; Şeşeoğulları Dirihan, Roda; Güven, Mehmet Esad; Oğuz Ahmet, Serra; Gutknecht, Norbert; Tezvergil Mutluay, Arzu (Springer, 2022)
Purpose: The objective of this study was to determine the effect of dental laser (DL) irradiation on the metalloproteinases (MMP)-mediated dentin collagen degradation. Methods: Human dentin disks were prepared (0.3 × 5x6mm, n = 60) and subjected to different treatments (n = 10/group): (1) control group (no treatment); (2) application of 37% phosphoric acid (PA) for 15 s; (3) irradiation with Er:YAG laser (120 mJ, 10 Hz); (4) irradiation with Er:YAG laser (120 mJ, 20 Hz); (5) irradiation with Er,Cr:YSGG laser (130mj, 30 Hz); and (6) irradiation with Er,Cr:YSGG laser (80mj, 50 Hz). After treatment, the total MMP activity and dry mass of each beam were measured, and after rehydration, they were incubated in 1 mL calcium- and zinc-containing incubation media for (a) one week and (b) three weeks. After each time point, dry mass changes were reassessed, and the aliquots of the incubation media were analyzed for pyridinoline-cross-link-containing degradation fragment of the C-terminal telopeptide of type I collagen (ICTP) using ELISA kits. All data were compared using ANOVA and Tukey’s test. Results: ANOVA showed significant differences among tested groups (p < 0.001). Laser-treated beams showed 55–75% less activity compared to 37% phosphoric acid-treated beams. The highest ICTP values were seen when PA was applied to the dentin surface in both time periods (p < 0.05). DL irradiation, be it with Er:YAG or Er,Cr:YSGG laser, did not increase the ICTP values in both time periods when compared with the control group (p > 0.05). Conclusion: The MMP-mediated dentin collagen degradation was the highest when PA was applied to the dentin surface and the lowest in Er:YAG or Er,Cr:YSGG laser-treated dentin groups in both time periods.
Keywords: Dentin; Er,Cr:YSGG Laser; Er:YAG Laser; MMP